PENERAPAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI TURUS KELAS III SD - Agnesia Odilia; Janet Retno; Natassya Elwina; Septiani; Solindar; Sri Wahyuni; Hamdani; Saminem; Marlina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low mathematics learning outcomes of third-grade elementary school students, particularly on the topic of poles, are influenced by several factors, such as lack of learning motivation, diverse thinking skills, and uninteresting teacher learning methods. This study aims to improve third-grade elementary school students' mathematics learning outcomes on the topic of poles through the application of differentiated learning. This study is a classroom action research (CAR) model that adopts the Kemmis and McTaggart cycle model. The study was conducted in two cycles, each encompassing planning, action implementation, observation/testing, and reflection. The subjects were 28 third-grade elementary school students, consisting of 15 boys and 13 girls. Data analysis was carried out in an integrated manner by calculating the class average (mean) and the percentage of student learning completion. The results showed a significant increase in students' mathematics learning outcomes after the implementation of the differentiated learning approach. In the pre-cycle conditions, the class average score was only 68, with a completion percentage of 28%. Following the interventions in Cycle I, the class average score increased to 71.79, with a 60% completion rate. Improvements in Cycle II, using concrete media, structured exercises, and intensive mentoring, significantly increased the class average score to 98.7, with a 100% classical learning completion rate. Based on these results, it can be concluded that the effective implementation of differentiated learning can improve mathematics learning outcomes for third-grade elementary school students.